Movimento estudantil universitário de Sergipe : modelos de organização, redes sociais e engajamento individual (2000-2015) - Santos, Adrielma Silveira Fortuna dos (2016)
This dissertation analyzes the forms of organization of the student movements of the UFS during the period 2000 to 2015. This is more particularly investigate how organizational models and repertoires used by student leaders and the Central Directory of Students former presidents are related changes in political, social networks these actors and individual engagement logic. Dialoguing with a theoretical framework that investigates the organizational dynamics, this study aimed to understand the relationship between the individual engagement, social networks and the choice of certain organizational models and repertoires used by different 13 managements DCE / UFS during the investigated period. Breaking with approaches that analyze the individual engagement as a streamlined and co-option process, we used theories and concepts that comprise procedural and relational forms the engagement of individual actors in multiple spaces of political activism. Thus, we investigated the previous relationship networks, the different spaces of socialization, life experiences and also the changes in the political context that factors which influenced the construction of the organizational models used by managements investigated. The empirical universe considered are the student movements that are organized at the Federal University of Sergipe. To account of the issues raised, this work is divided into four parts: the first is to analyze, from the desk research, the emergency conditions of the University Student Movement in Sergipe, the causes defended, organizational repertoires used and the student movements, between the period 1950 and 1999, focusing mainly in the 1980s and 1990s; the second part examines based on questionnaires and the method previously mentioned, the profile of students who are active, focusing mainly on the militant and political itinerary. Also, investigates three significant areas: the CAs, the Student Assemblies and the CEB's; the third part deals with the process of formation and performance of a DCE management, and how this process mobilizes interpersonal networks of leaders and a political dispute over this space that goes beyond the walls of the University; the fourth part discusses the militants careers of DCE former presidents in the last 15 years, whereas the social origin, the multiple engagements and socialization processes and identification with militancy influenced the transformation of the organizational models used by them. This thesis has allowed to show that the organizational models used is directly linked to changes in the political context, the multiple engagement and the construction of dense social networks and socialization processes that promote continuity in militancy. It also shows that the relationship between student movements and political parties, is both confrontational and conciliatory in the face of financial interests, electoral and representative of both parties. In addition, this paper argues that the engagement of activists and student leaders in political parties stems from a personal and professional identification process of the actors themselves, as they make the associative militancy and partisan a life project.